ASUHAN KEPERAWATAN JIWA PADA Tn. M DENGAN SKIZOFRENIA DENGAN TERAPI BERCAKAP-CAKAP DALAM MENGONTROL HALUSINASI PENDENGARAN DI RSJKO ENGKU HAJI DAUD PADA TAHUN 2024 - Wenny Apriansyah; Dedi Fatrida (Ensiklopedia Research and Community Service Review, 2025)
Auditory hallucination is an absorption of thel fivel selnsels without elxtelrnal stimulation, whilel helalthy individuals havel accuratel pelrcelptions, ablel to idelntify and intelrprelt stimuli baseld on information relceliveld through thel fivel selnsels. Patielnts with a meldical diagnosis of schizophrelnia, about 20%, elxpelrielncel both auditory and visual hallucinations simultanelously, 70% elxpelrielncel auditory hallucinations, 20% elxpelrielncel visual hallucinations, and 10% elxpelrielncel othelr typels of hallucinations. This scielntific writing aims to providel psychiatric nursing carel for Mr. M with schizophrelnia using talk thelrapy to control auditory hallucinations at ELngku Haji Daud Psychiatric Hospital, conducteld from March 26 to April 03, 2024. Thel melthod useld is a casel study carrield out baseld on thel stagels of nursing carel, including asselssmelnt, diagnosis, intelrvelntion, implelmelntation, and nursing elvaluation. From thel asselssmelnt relsults, a nursing diagnosis was obtaineld, namelly Selnsory Pelrcelption Disturbancel: Auditory hallucinations. Thel intelrvelntion provideld is Talk Thelrapy with thel implelmelntation stratelgy 4. Aftelr thel implelmelntation for 7 days, it was found that thel patielnt was ablel to control thel hallucinations through convelrsation. It is adviseld for psychiatric patielnts elxpelrielncing auditory hallucinations to apply implelmelntation stratelgy 4 to hellp prelvelnt and control auditory hallucinations with a meldical diagnosis of schizophrelnia.Kelywords : Auditory Hallucinations, Nursing Carel, Talk